Constraining Bankruptcy as an Ultimum Remedium: Evidence from Indonesia in Comparative Perspective with the United States and Singapore - Santosa, Dewa Gede Giri; Dewi, Erna; Fardiansyah, Ahmad Irzal (International Journal of Business, Law, and Education, 2026)
Bankruptcy law is fundamentally designed as an ultimum remedium due to its severe legal and economic consequences for debtors, creditors, and broader market stability. However, Indonesian bankruptcy law continues to rely on minimal formal requirements, which may facilitate the misuse of bankruptcy petitions against solvent debtors. This article examines how the principle of ultimum remedium and proportionality has been operationalized in judicial practice through Indonesian Supreme Court Decision No. 1714 K/Pdt.Sus-Pailit/2022. Using a normative legal approach combined with jurisprudential analysis, this study evaluates the Court’s reasoning in limiting bankruptcy despite the formal statutory requirements being satisfied. The analysis is complemented by a comparative perspective with involuntary bankruptcy regimes in the United States and the rehabilitative-oriented insolvency framework in Singapore. The findings demonstrate a judicial shift from formalistic application toward substantive justice, emphasizing economic impact, proportionality, and the availability of non-bankruptcy alternatives. This development signifies an emerging judicial constraint on bankruptcy as a last resort and provides a normative foundation for future reform of Indonesian bankruptcy law.